A method for calculating low-temperature stress-strain curves of austenitic stainless steels. (April 2020) - Ding, Huiming; Wu, Yingzhe; Lu, Qunjie; Zheng, Jinyang
Highlights: Similar characteristics are found for different austenitic stainless steels at 77–293 K. Empirical relations between low-temperature material model parameters and mechanical properties are founded. A calculating method for low-temperature stress-stain curves of austenitic stainless steels is proposed. Abstract: Low-temperature stress-strain curves of austenitic stainless steels are essential for cryogenic pressure vessels' elastic-plastic stress analysis. But, the method that how to get the low-temperature stress-strain curves is still missing in the current pressure vessel standards. To resolve this problem, related work is carried out based on 351 sets of tensile data of 15 austenitic stainless steels. Similar characteristics of low-temperature stress-strain curves in the phase composition, martensitic transformation and curve shape are found. Thus, the same low-temperature material model can be adopted for different austenitic stainless steels. Furthermore, the empirical relations between low-temperature material model parameters and mechanical properties ( R p0.2, R m and A ) are founded. Finally, a calculating method for low-temperature stress-stain curves of austenitic stainless steels is proposed based on the empirical relations and low-temperature material model. Compared with experimental curves, the calculated stress-strain curves show similar shape characteristics and is also of uniqueness and conservation. This is of important significance to the light-weight design of cryogenic pressure vessels.